The Effects of Coronavirus Disease 2019 Outbreak on Medical Students - Bilgi, Kadir; Aytaş, Gamze; Karatoprak, Utku; Kazancıoǧlu, Rümeyza; Özçelik, Semra (Frontiers in Psychiatry, 2021)
Introduction: The Covid-19 pandemic has influenced the whole world and after the first case was diagnosed in Turkey, educational activities were suspended, and partial curfews were implemented. This study was conducted to assess the concerns faced by the medical students about their professional life, due to the disrupted educational activities and related psychological effects. Methods: This is a cross-sectional survey study, conducted with self-administered questionnaires on Bezmialem Vakif University medical students, during the pandemic. The questionnaire consists of questions about demographics, environmental factors, GAD-7, and PHQ-9 scales. Results: A total of 178 students participated in the study. The Female to male ratio of the participants was 5:2. 19,7% of the respondents were experiencing severe anxiety, 17.4% moderate anxiety, and 37.1% mild anxiety according to the GAD-7. 13,5% of the respondents were experiencing severe depression, 21.9% moderate-severe depression, and 23% mild depression according to the PHQ-9. There was no statistically significant difference between the grades in terms of GAD-7 or PHQ-9 scores. Male participants were more likely to have suicidal thoughts. (p = 0.013) According to our study, the factors with the highest influence on students were respectively: “Major changes in personal life”, “Disruption in educational activities” and “Covid-19 related anxiety of loss of relatives and contamination or infection”. Women gave on average higher points to “Covid-19 related anxiety of loss of relatives and contamination”. Conclusions: We found that a significant portion of students regardless of their year in medical school were profoundly affected by the pandemic process as is shown by their anxiety and depression scores. The disruption in educational activities is one of the main factors of these effects and we believe these should not be ignored as it could lead in the future to a series of problems for Medical education and students alike.